New global maximum power point tracking and modular voltage equalizer topology for partially shaded photovoltaic system / Immad Shams - Immad , Shams (2022)
Maximum power point tracking (MPPT) is one of the crucial components to ensure the PV system operates optimally. The bypass diodes are added across series-connected PV modules to avoid the hotspot phenomenon on the surface of the solar cells, which resulted in the multiple peaks on the power-voltage curve during partial shading conditions (PSCs). The conventional MPPT algorithms are unable to track the global maximum power point (GMPP) for all the complex PSCs and are often stuck at local maximum power point (LMPP). To deal with PSCs, controller-based and circuit-based solutions have been provided in the literature. In this work, different areas have been identified, considering both approaches, on which further research has been carried out. In terms of controller-based, in this work, a new global maximum power point tracking (GMPPT) algorithm based on a modified butterfly optimization algorithm (MBOA) has been proposed. The proposed method differentiates between different PSCs, uniform shading conditions (USCs), solar intensity, and load variation conditions with fast convergence speed (CS). Only one dynamic variable is used as a tuning parameter reducing the complexity of the algorithm. The search space skipping method has been proposed to improve the CS. The proposed method is hybridized with a constant impedance method to improve the system's response time for fast varying load variations. The proposed method has been validated experimentally on SEPIC converter topology with a sampling time of 0.05 s. The experimental validation proved the average tracking time for different shading patterns is less than 1 s with a steady-state efficiency of 99.74% on average. The CS for USCs is improved by 40.35%. The response to load variation is also improved by 86.15% and becomes eligible for fast varying load variations. Lastly, the comparison table based on the MPPT rating has been presented to determine the effectiveness of the proposed method among other popular metaheuristic approaches used for GMPPT. Despite the effective proposed GMPPT algorithm, the PSCs reduce the maximum power extraction capability of the PV system heavily due to the activation of bypass diodes. To enhance the energy yield during PSCs, in this work, a hybridized switched inductor and switched capacitor converter (SCC-SIC) based voltage equalizer (VE) topology has also been proposed to prevent the multiple peaks during PSCs and increase the energy yield. MPPT controller with PSC detection, which uses only one voltage and one current sensor, is proposed so that the VE can only operate when the MPPT controller senses the PSC to avoid the undesired loss of MOSFET and diode due to switching and conduction. The performance evaluation determined the efficacy of the proposed system with the other state-of-the-art modular PV equalizers for ten modules in series with the reduction in switch count. The experimental results showed an increase in energy yield of 30.42% on average. In addition, the proposed controller tracks the MPP for USCs at 0.10 s while for PSCs at 0.692 s with an MPPT efficiency of 99.67% on average. Lastly, the MBOA-MPPT controller for GMPPT and the proposed controller for VE have been compared under the same test conditions. It has been observed that the proposed controller for VE topology enhanced the energy yield by 30.03% and tracking time less than 1 s with less oscillation of power during the tracking state. Still, the cost of the system is higher in comparison with the conventional system for GMPPT.